Bioprodutos derivados de biomassa vegetal no combate ao mosquito transmissor da dengue - Aedes aegypti - Esmeraldo, Milena Alencar (2016)
The Aedes aegypti mosquito is the main vector responsible for the spread of diseases like Chikungunya Fever, Zika and Dengue. Due to the absence of an effective vaccine for all kinds of diseases, the control is still accomplished through the elimination of potential mosquito breeding grounds by applying larvicides during the period of transmission. Regarding to pesticides, the most used are becoming obsolete due to the emergence of resistant strains of mosquitoes. Given this context, this study aimed at obtaining, characterizing and testing bioproducts to selective control of larvae and eggs of Aedes aegypti, adding value to the plant biomass, more precisely the Cashew Nut Shell Liquid technical and natural and constituents cardanol, cardol acting as core material and galactomannans derived of the endosperm of seeds of Adenanthera pavonina L. species as encapsulant. Encapsulated bioproducts, obtained by spray drying Spray Dryer, were characterized by spectroscopy Scanning Electron Microscopy - SEM, Thermogravimetric analysis - TG, Dynamic Light Scattering - DLS and through the kinetic profiles of release in vivo and in vitro. Laboratory bioassays were performed with larvae of the 3rd stage Aedes aegypti mosquito at different concentrations (10 - 20 - 40 – 80 -100 – 200 - 400 - 800 - 1000) ppm of bioproducts. Above 200 ppm concentration all bioproducts showed mortality rates above 80%, mainly noted for LCC natural, and the percentage considered acceptable by the World Health Organization - WHO to larvicides. Biological assays oviposition and ovicidal activity in the concentration range (200 - 500 - 800) ppm were also performed showing percentage repellence oviposition above 60% and low rates of hatching eggs and larvae growth. These results bring good prospects regarding the use of bioproducts in combat / control the mosquito Aedes aegypti suggesting potential applications in the precepts of Green Chemistry.